The Palgrave handbook of linguistic (im)politeness - Culpeper, Jonathan; Haugh, Michael; Kádár, Dániel Z. (Palgrave Macmillan, 2017)
This handbook comprehensively examines social interaction by providing a critical overview of the field of linguistic politeness and impoliteness.Authored by over forty leading scholars, it offers a diverse and multidisciplinary approach to a vast array of themes that are vital to the study of interpersonal communication.